Backstress shift modelling concept for improving uniaxial ratcheting predictions for wrought 304 stainless steel and additively manufactured Inconel 718 - Adamec, Tomáš; Hassan, Tasnim; Zapletal, Josef; Kondepati, Sudhir Kumar; Šebek, František (Elsevier, 2025)
The Chaboche model is one of the widely used models, but it still shows limitations in predicting various complex responses. For example, issues in predicting ratcheting responses of metals and alloys under stress-controlled loading, especially under uniaxial cyclic loading, have been demonstrated. Therefore, this study evaluates the performance of the Chaboche model under uniaxial cyclic loading with an emphasis given to the simulation of uniaxial ratcheting responses. A modification to the model is proposed to enhance its prediction of the uniaxial ratcheting response for a wide range of ratcheting rates. The modification technique is called the backstress shift model, developed on the basis of experimental observations of the similarity between the strain- and stress-controlled hysteresis loops. A backstress memory surface is introduced and its material parameters are calibrated using responses of stainless steel 304 and Inconel 718 superalloy. For this study, data for steel are collected from the literature and experiments are performed on superalloy to acquire a set of data for development and validation of the proposed model. The modified model demonstrates better predictability of the uniaxial ratcheting responses compared to the Chaboche model with the threshold, especially for the additively manufactured nickel-based superalloy. The modified model also works well for the wrought 304 stainless steel.

The Chaboche model is one of the widely used models, but it still shows limitations in predicting various complex responses. For example, issues in predicting ratcheting responses of metals and alloys under stress-controlled loading, especially under uniaxial cyclic loading, have been demonstrated. Therefore, this study evaluates the performance of the Chaboche model under uniaxial cyclic loading with an emphasis given to the simulation of uniaxial ratcheting responses. A modification to the model is proposed to enhance its prediction of the uniaxial ratcheting response for a wide range of ratcheting rates. The modification technique is called the backstress shift model, developed on the basis of experimental observations of the similarity between the strain- and stress-controlled hysteresis loops. A backstress memory surface is introduced and its material parameters are calibrated using responses of stainless steel 304 and Inconel 718 superalloy. For this study, data for steel are collected from the literature and experiments are performed on superalloy to acquire a set of data for development and validation of the proposed model. The modified model demonstrates better predictability of the uniaxial ratcheting responses compared to the Chaboche model with the threshold, especially for the additively manufactured nickel-based superalloy. The modified model also works well for the wrought 304 stainless steel.
Backstress shift modelling concept for improving uniaxial ratcheting predictions for wrought 304 stainless steel and additively manufactured Inconel 718
Keywords: Cyclic hardening; Cyclic softening; Evolutionary algorithm; Isotropic hardening; Uniaxial ratcheting; Cyclic hardening; Cyclic softening; Evolutionary algorithm; Isotropic hardening; Uniaxial ratcheting